Novel ecosystems : intervening in the new ecological world order - Hobbs, R. J. (Richard J.); Higgs, Eric, 1958-; Hall, Carol M. (John Wiley & Sons, 2013)
This book brings researchers from a range of disciplines together with practitioners and policy makers to explore the questions surrounding novel ecosystems. It includes chapters on key concepts and methodologies for deciding when and how to intervene in systems, as well as a rich collection of case studies and perspective pieces.